PANRITA LOPI: Cultural Value and Religiosity Behind Professionalism of Making Pinisi Boats in Bulukumba - Eymal B Demmalino; Tamzil Ibrahim; Yopie Lumoindong (ETNOSIA : Jurnal Etnografi Indonesia, 2019)
The main of this article to be expressed are Cultural Values and the Religiosity Behind the Skills (Kepanritaan) of Pinisi Boat Making in a very well-known community of boat makers in Ara, Bira and Tanalemo Villages, Bontobahari District, Bulukumba Regency, South Sulawesi. This research uses the verstehen method (Weber in Ritzer and Goodman, 2004 and Kaelan, 2005) on Pinisi Boat Making Activities and Changes from the beginning to the era of shipping modernization. The data was collected by combining comprehensive data collection techniques (observation, in-depth interviews, documentation, and triangulation: Sugiyono, 2007) and analyzed using interpretive post positivistic qualitative descriptive analysis method (with systemic complementary analysis procedures: Data Collection), Grouping, Categorization, and Discarding Insignificant Data (Data Reduction), Mapping Data on Causality between Data Categorization, and Conclusion: Miles and Huberman, 1995). The results of the research show that the professionalism in making pinisi boats is built on the basis of assessment with the underlying occult values. A cultural value that tends to be ecologically oriented in the sense of keeping the relationship harmonious with the natural ruler in a magical way. These values tend to weaken amid the development of shipping modernization and the development of the boat-making industry.